ANALISIS JARINGAN KOMUNIKASI PADA AKUN @KEMENKESRI DI MEDIA SOSIAL TWITTER - Sri Wahyuni; Yohanes Arie Kuncoroyakti; Muhammad Ariq S.M (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The purpose of this study was to examine what the communication network structure is like at the stakeholder level when reporting on COVID-19 vaccination via the social media Twitter. This research method uses descriptive and quantitative data analysis techniques for social network analysis by running data collection techniques via netlytic.org and analyzing using gephi 0.9.2 software. The theory used in this study is computer-mediated communication theory. As a result, it turns out that the six attackers I contacted the most were @assumco, @ismailfahmi, @kimberley20101, @polisi_jatim, @kompascom, and @kemenkesRI. This means that the @assumco account is the most mentioned attacker in his Covid-19 vaccination news from @kemenkesRI Twitter account. Closenness Centrality has 568 perfectly positioned actors with a score of 1.0. In other words, a perfect score indicates that attackers find it easy to spread information over the network. For Eigenvector Centrality, the @kemenkesRI account has a score of 1.0. According to the Ministry of Health account, it can be concluded that this he is the opinion leader who provides the most accurate and reliable information on Covid-19 vaccination and is the most powerful and most popular player.